2018
DOI: 10.1007/s00405-018-5127-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cochlear implantation on the management strategy of patients with neurofibromatosis type 2

Abstract: CI is an effective option in auditory rehabilitation and should be considered primarily for NF2 patients with intact cochlear nerve. EPS might be a predictor for cochlear implant performance. Good contralateral hearing may present a barrier to daily use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…4 Since that time, additional data have emerged supporting safe and effective cochlear implantation in patients with unresected vestibular schwannomas following treatment with radiation or a period of observation of small, stable schwannomas. 2,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Our study aims to compile the current data regarding hearing outcomes for cochlear implantation in ears with non-operated tumors and also add to the recent growing body of evidence with this multi-center series.…”
Section: Introductionmentioning
confidence: 99%
“…4 Since that time, additional data have emerged supporting safe and effective cochlear implantation in patients with unresected vestibular schwannomas following treatment with radiation or a period of observation of small, stable schwannomas. 2,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Our study aims to compile the current data regarding hearing outcomes for cochlear implantation in ears with non-operated tumors and also add to the recent growing body of evidence with this multi-center series.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the results are less good than in non-tumor patients needing an acoustic implant 10 . In few selected cases and series, good results could be reported with CI in NF2 23 with speech discrimination up to 63% in 10 of 12 patients. Lloyd et al found better benefit from CI, if the related tumor was neither treated by surgery nor by radiosurgery 8 .…”
Section: Discussionmentioning
confidence: 92%
“…In most cases, ABI was implanted on the only hearing side, although in some cases it was implanted on the first side with the device switched off until contralateral total hearing loss was present (Sleeper ABI) 16 . The ABI showed the expected auditory benefit with lip-reading aid in most cases.…”
Section: The View Of the Expert: A Free Choice Topicmentioning
confidence: 99%
“…In conclusion, these three IVS cases were initially treated in the early 2000s by surgical removal which might not be at the present time the first-line treatment for NF2 apart from cases with life-threatening large VS (26,27). However, this study demonstrates that removal of IVS with concomitant CI implantation provides a long-term benefit from CI, although it could be altered by the occurrence of other intracanalicular and/or CPA NF2-related tumors, the treatment of which might restore the initial CI benefit.…”
Section: Discussionmentioning
confidence: 96%